Geological setting, petrology and mineralogy of metabasites in a thermal aureole of Tanvald granite (northern Bohemia) used for the manufacture of Neolithic tools - Sida,P.; Kachlik,V. (Journal of Geosciences, 2009)
This study examined the metabasites in a thermal aureole of the Tanvald granite in the northern part of the Bohemian Massif that were used for manufacturing Neolithic tools. The metabasites form relatively thin bodies from several cm to 2 m thick and are intercalated conformably within the host metasedimentary rocks. Two types of thermally metamorphosed actinolite-hornblende hornfelses (metabasites) were distinguished: 1) fine-grained amphibole-rich metabasite and 2) metabasites with relicts of porphyritic texture. Because of their large lateral extent and geological setting within metasediments, fine-grained metabasites may correspond to former volcanoclastic rocks (meta-tuffs), while the porphyritic metabasites probably represent metamorphosed dolerite sills or dykes. The host rocks are various types of cordierite-biotite spotted schists or andalusite-cordierite-biotite hornfelses. Both groups of metabasites consist of several types of amphiboles, calcic plagioclase (andesine to labradorite) and ilmenite, variably replaced by their alteration products. Apatite, alteration products of ilmenite, magnetite and sulphides are common accessory phases, while epidote and titanite are present only rarely. Relicts of magmatic minerals and minerals from older metamorphic stages are scarce. The peak contact metamorphic conditions were constrained between 540 and 600 °C. Sample of charcoal taken from the base of the Neolithic quarry, where a large amount of waste from making of semi-finished polished tools was found, was dated by radiocarbon dating technique. It gave an age of VERA-2981 6120 ± 35 BP, which places the sampling location in one of the closing stages of quarrying in this part of the site.The correspondence of the petrological and mineralogical characteristics of metabasites from the thermal aureole and stone tools found in Germany and southern Moravia provided evidence that Neolithic tools were traded over distances of several hundred kilometres.
Keywords: amphibole hornfels; stone tool; Neolith; Tanvald granite; Krkonose-Jizera Crystalline Unit; Bohemian Massif